THE ADVANTAGE OF PREDICTION IN SIMULTANEOUS INTERPRETING (American Journal of Interdisciplinary Research and Development, 2022)
This article is devoted to the problems of using probability prediction strategy in simultaneous interpretation. In addition, the article also analyzes the probability prediction model in simultaneous translation. It then posits a role for the production system in prediction during comprehension and develops a theoretical framework for prediction-by-production in simultaneous interpreting that has implications for our understanding of prediction during language comprehension.